2017
DOI: 10.1007/s00737-017-0738-5
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of depressive symptoms during pregnancy

Abstract: Recently, the US Preventive Services Task Force has advocated to screen pregnant and postpartum women for depression. However, we questioned the meaning of a single elevated depression score: does it represent just one episode of depression or do these symptoms persist throughout the entire pregnancy? This study assessed depressive symptoms at each trimester in a cohort of 1813 pregnant women and evaluated whether women with different patterns of depressive symptoms showed other characteristics. Depending on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 35 publications
2
19
2
2
Order By: Relevance
“…This might associate with the number of included studies during different trimesters, the pooled prevalence was high where large number of studies included and low where small studies were included as adjustment was not made on the number of studies. Consistent with our findings, one study reported an increased pattern of depression from the first to the second trimester due to increases in a range of risk factors during the three trimesters of pregnancy [113]. Further study could assist in prevention planning in identifying the appropriate timing and frequency of screening and intervention.…”
Section: Discussionsupporting
confidence: 89%
“…This might associate with the number of included studies during different trimesters, the pooled prevalence was high where large number of studies included and low where small studies were included as adjustment was not made on the number of studies. Consistent with our findings, one study reported an increased pattern of depression from the first to the second trimester due to increases in a range of risk factors during the three trimesters of pregnancy [113]. Further study could assist in prevention planning in identifying the appropriate timing and frequency of screening and intervention.…”
Section: Discussionsupporting
confidence: 89%
“…Considering the PI subscale items, women without a partner (n = 12) were excluded from the analysis. A final sample of 1739 women were suitable for analysis, and of whom the characteristics (demographics, lifestyle habits, obstetrics, and psychiatric history) were not different from the original sample as published elsewhere in the current journal (Truijens et al 2017), in which scores of the Edinburgh (Postnatal) Depression Scale (E(P)DS; Cox et al 1987) were also repeatedly assessed at all trimesters. The study was approved by the Psychology Ethics Committee of Tilburg University (protocol number EC-2012.25).…”
Section: Methodsmentioning
confidence: 99%
“…Antepartum depressive symptoms and subclinical depression with prevalence rates ranging from 10 to 20%, often remain unnoticed by maternity care providers during antenatal visits [ 1 ]. However, early detection is crucial because symptoms of depression or anxiety may result in antepartum depression with prevalence rates ranging from 5 to 13% or in postpartum depression (PPD) with prevalence rates of 10 to 15% [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%